2022
DOI: 10.3389/fdgth.2021.662343
|View full text |Cite
|
Sign up to set email alerts
|

Explainable Machine Learning for COVID-19 Pneumonia Classification With Texture-Based Features Extraction in Chest Radiography

Abstract: Both reverse transcription-PCR (RT-PCR) and chest X-rays are used for the diagnosis of the coronavirus disease-2019 (COVID-19). However, COVID-19 pneumonia does not have a defined set of radiological findings. Our work aims to investigate radiomic features and classification models to differentiate chest X-ray images of COVID-19-based pneumonia and other types of lung patterns. The goal is to provide grounds for understanding the distinctive COVID-19 radiographic texture features using supervised ensemble mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Kurtosis is one of first-order features that is used to compute of the “peakedness” of the distribution of the values. Luís et al [ 43 ] confirmed that COVID-19 induces consolidation and ground glass opacification, resulting in lower kurtosis values and flatter peak.…”
Section: Discussionmentioning
confidence: 99%
“…Kurtosis is one of first-order features that is used to compute of the “peakedness” of the distribution of the values. Luís et al [ 43 ] confirmed that COVID-19 induces consolidation and ground glass opacification, resulting in lower kurtosis values and flatter peak.…”
Section: Discussionmentioning
confidence: 99%
“…Luís et al . [40] confirmed that COVID-19 induces consolidation and ground glass opacification, resulting in lower kurtosis values and flatter peak.…”
Section: Discussionmentioning
confidence: 90%
“…Moura et al . [40] observed more heterogeneity of GLRLM in the upper left region of COVID-19 class which may be due to consolidation that tended to diffuse. Pizzi et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations